Citrus Tissue Culture : AUXINS IN RELATION TO ABSCISSION IN EXCISED PISTILS - Einset, John W. (1981)
An in vitro bioassay for chemicals that affect Citrus abscission was used to identify three inhibitors of stylar abscission in lemon pistil explants incubated on defined nutrient media. The three inhibitors (picloram, 4-chlorophenoxyacetic acid, and 3,5,6-trichloropyridine-2-oxyacetic acid) are all auxins, and the most potent of them (i.e. picloram) was found to be at least 10 times more active in the bioassay than 2,4-dichlorophenoxyacetic acid. Picloram (2 micromolar) also was shown to be effective in inhibiting stylar abscission in pistil explants from other Citrus cultivars such as mandarin, Valencia, and Washington navel oranges and grapefruit. To study the physiology of auxins active as abscission inhibitors versus inactive auxins in lemon pistils, the transport and metabolism of [1-(14)C]-2,4-dichlorophenoxyacetic acid was compared with that of [2-(14)C]indole-3-acetic acid, which is without effect in the bioassay over the range from 0.1-100 micromolar. Insignificant quantities of labeled indole-3-acetic acid and/or labeled derivatives were found to reach the presumptive zone of stylar abscission under the test conditions. Labeled 2,4-dichlorophenoxyacetic acid and/or labeled derivatives also were transported slowly through pistils, but some radioactivity could be detected in the stylar abscission zone as early as 24 hours after the start of incubation. Extensive conversion of [2-(14)C]indole-3-acetic acid to labeled compounds tentatively considered to be glycoside and cellulosic glucan derivatives was found with the use of solvent extraction methodology. A significantly smaller percentage of the radioactivity in pistils incubated on [1-(14)C]-2,4-dichlorophenoxyacetic acid was found in fractions corresponding to these derivatives. Both transport and metabolism appear to be important factors affecting the activity of auxins as abscission inhibitors in the bioassay.